Cyclic and Acyclic Amine Oxide Alkyl Derivatives as Potential Adjuvants in Antimicrobial Chemotherapy against Methicillin-Resistant Staphylococcus aureus with an MDR Profile - Lorenza Fagnani; Lisaurora Nazzicone; Fabrizia Brisdelli; Luisa Giansanti; Sara Battista; Roberto Iorio; Sabrina Petricca; Gianfranco Amicosante; Mariagrazia Perilli; Giuseppe Celenza; Pierangelo Bellio (MDPI AG, 2021)
The dramatic intensification of antimicrobial resistance occurrence in pathogenic bacteria concerns the global community. The revitalisation of inactive antibiotics is, at present, the only way to go through this health system crisis and the use of antimicrobial adjuvants is turning out the most promising approach. Due to their low toxicity, eco-friendly characteristics and antimicrobial activity, amphoteric surfactants are good candidates. This study investigated the adjuvant potentialities of commercial acyclic and newly cyclic N-oxide surfactants combined with therapeutically available antibiotics against MDR methicillin-resistant Staphylococcus aureus (MRSA). The safety profile of the new cyclic compounds, compared to commercial surfactants, was preliminarily assessed, evaluating the cytotoxicity on human peripheral mononuclear blood cells and the haemolysis in human red blood cells. The compounds show an efficacious antimicrobial activity strongly related to the length of the carbon atom chain. In drug-drug interaction assays, all surfactants act synergistically, restoring sensitivity to oxacillin in MRSA, with dodecyl acyclic and cyclic derivatives being the most effective. After evaluating the cytotoxicity and considering the antimicrobial action, the most promising compound is the L-prolinol amine-oxide C12NOX. These findings suggest that the combination of antibiotics with amphoteric surfactants is a valuable therapeutic option for topical infections sustained by multidrug-resistant S. aureus.